INOVASI KURIKULUM LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN PERGURUAN TINGGI AGAMA ISLAM - Nur Ali (Fak. Tarbiyah UIN Maliki Malang, 2012)
The Minister of national education and The Minister of religious affair have decreed that the teacher must have a certain academic qualification and competencies, and teacher certification if he/she wants to become a professional teacher. Beside that, the academic competencies of teacher and its certification have to appropriate with the competencies standard of curriculum in the school. So, the institution of educational manpower education in the Islamic higher education (IHE) has to be able to realize the policies by conducting the curriculum innovation based on the policies of education and the needs of stake holders and the religious character of IHE. There are seven model of innovation can be used (i) incremental, (ii) radical, (iii) modular, (iv) architectural, (v) top-down model, (vi) bottom-up model, and (vii) model of N-3; niteni, niroake and nambahake. The process of innovation include; (i) recognizing a problem or need, (ii) research, (iii) development, (iv) commercialization, (v) deffusion and adoption, dan (vi) conceguences. The approaches of curriculum innovation are (i) produktive, (ii) humanistic, (iii) democration, (iv) clasic, (v) romantic, and (vi) modern. The strategies in curriculum innovation are the rational-Empirical Strategy, the normal-Reeducative Strategy, and the Power-Coercive Strategy.